1973
DOI: 10.1002/bjs.1800600313
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the vagus nerves on the biliary system

Abstract: Vagotomy has become accepted as a standard operation for the treatment of peptic ulcer during the past 15 years. Although used to treat a specific lesion in the stomach or duoddenum, vagus division can have a much wider effect on the digestive system, but little attentionhas been paid by most surgeons to the efffects of the vagus on other organs and it is timely to review the influence of the vagus nerves on the biliary system. In 1887 Ruggero Oddi suggested that the sphincter which is named after him was part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…In the present study, although the cannulae inserted in the common bile duct were tied with its wall containing the neurons on the serosa (Hopton, 1973), caerulein induced the relaxation response on the SO in the preoperative and sham operated dogs. That the excitatory response of the SO to caerulein was only induced by gastrectomy indicates that the SO motility was reflexly controlled by the neuronal regulation from the stomach and/or uppermost duodenum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, although the cannulae inserted in the common bile duct were tied with its wall containing the neurons on the serosa (Hopton, 1973), caerulein induced the relaxation response on the SO in the preoperative and sham operated dogs. That the excitatory response of the SO to caerulein was only induced by gastrectomy indicates that the SO motility was reflexly controlled by the neuronal regulation from the stomach and/or uppermost duodenum.…”
Section: Discussionmentioning
confidence: 99%
“…If the reversed response to caerulein was induced by cholecystrectomy alone (Rolny et al, 1986) and sectioning of the nerves surrounding the common bile duct (Hopton, 1973), the reversed response should have been indicated after tying the common bile duct with cannula in the normal and sham operated dogs in the present experiment. However, caerulein induced the relaxation response on the SO after tying the cannulae with its wall of the common bile duct.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastrectomy has been considered as another risk factor for cholelithiasis . Truncal vagotomy during peptic ulcer surgery is associated with the development of cholelithiasis ,14. Hauters et al1 reported a high incidence of cholelithiasis (47%) after total gastrectomy and concluded that vagotomy performed during the resection may have contributed to the development of cholelithiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Truncal vagotomy results in gallbladder hypomotility, 1-12 biliary stasis, 1,[3][4][5][8][9][10][11][12] and various changes in bile composition, 5,[8][9][10][11][12][13][14][15] all of which were considered to enhance gallstone formation. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Total gastrectomy involves truncal vagotomy and is a high-risk procedure for the development of cholelithiasis. [1][2][3] As truncal vagotomy is an integral part of esophagectomy, we hypothesized that esophagectomy would also predispose to gallstone formation.…”
Section: Introductionmentioning
confidence: 99%